Research on intelligent modeling and policy making of CNC brain - Jun ZHOU; Keqing LIU; Shikui WANG; Ling YANG (Dianxin kexue)
As a future-oriented new network architecture, the core idea of computing and network convergence is to manage cloud-edge-end computing network resources in a centralized or distributed way by centering on the deep integration of computing force and network resources, so as to provide computing service for users’ needs.Although the CNC has made some progress in standard setting and industrial promotion, the overall development still faces many challenges, and there are still many scientific and engineering problems to be broken through.Research on CNC and its brain was carried out, the latest progress in related fields in the industry was analyzed, and the idea of building intelligent CNC brain was put forward, hoping to throw a brick at the table, jointly promote the implementation of AI in CNC, and truly realize intelligent CNC.